1994
DOI: 10.1128/aem.60.12.4339-4344.1994
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of chlorine penetration into biofilms during disinfection

Abstract: Transient chlorine concentration profiles were measured in biofilms during disinfection by use of a microelectrode developed for this investigation. The electrode had a tip diameter of ca. 10 microm and was sensitive to chlorine in the micromolar range. The biofilms contained Pseudomonas aeruginosa and Klebsiella pneumoniae. Chlorine concentrations measured in biofilms were typically only 20% or less of the concentration in the bulk liquid. Complete equilibration with the bulk liquid did not occur during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
158
2
13

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(177 citation statements)
references
References 15 publications
4
158
2
13
Order By: Relevance
“…Such transport limitation of biocide influx into the biofilm has been convincingly demonstrated for free chlorine at neutral pH. The profoundly retarded penetration of chlorine has been experimentally determined using a chlorine-sensitive micro-electrode in natural (de Beer et al 1994) and artificial Xu et al 1996) biofilm systems. The penetration time of free chlorine can be hundreds of times longer than for a similarly sized non-reactive solute.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such transport limitation of biocide influx into the biofilm has been convincingly demonstrated for free chlorine at neutral pH. The profoundly retarded penetration of chlorine has been experimentally determined using a chlorine-sensitive micro-electrode in natural (de Beer et al 1994) and artificial Xu et al 1996) biofilm systems. The penetration time of free chlorine can be hundreds of times longer than for a similarly sized non-reactive solute.…”
Section: Introductionmentioning
confidence: 94%
“…Biocides are widely used to control the detrimental formation of microbial biofilms, but their efficacy is always disappointing when compared with disinfection assays performed with planktonic micro-organisms (Costerton et al 1987;Brown and Gilbert 1993). The mechanisms by which biofilms resist disinfection are not all elucidated, but over the past few years, progress has been made in describing and quantifying the extent to which incomplete biocide penetration impacts biocide performance (de Beer et al 1994;Stewart and Raquepas 1995;Chen and Stewart 1996;Xu et al 1996). Retarded delivery of biocide into the biofilm occurs when the biocide is neutralized by reaction with biofilm constituents faster than it diffuses into the biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the EPS matrix may act as a diffusion barrier to delay the infiltration of some antimicrobial agents (Xu et al, 2000). The reactive chlorine species in a number of these agents may be deactivated at the surface layers of the biofilm before they are able to disseminate into the interior of the biofilm (de Beer et al, 1994). A recent study showed that oxacillin, cefotaxime, and vancomycin had reduced penetration throughout S. aureus and S. epidermidis biofilms (Singh et al, 2010).…”
Section: Principal Strategies In the Management Of Biofilmsmentioning
confidence: 99%
“…Biofilm resistance to chlorine is still incompletely understood, but is at least partly because of hindered penetration of the biocide into the biofilm (De Beer et al 1994;Chen and Stewart 1996;Xu et al 1996). Active chlorine concentrations as high as 1000 ppm are necessary for a substantial reduction in bacterial numbers in multispecies biofilms (formed by L. monocytogenes, Ps.…”
Section: Implications Of Biofilm Formationmentioning
confidence: 99%
“…pneumoniae and Ps. aeruginosa were typically only 20% or less of the concentration in the bulk liquid (De Beer et al 1994). The slow or incomplete penetration of the biocide into the biofilm is partly because of diffusion limitation in the exopolymeric matrix, but primarily because of neutralization of the active compound in the outermost regions of the matrix.…”
Section: Implications Of Biofilm Formationmentioning
confidence: 99%